Regions required for CD4 binding in the external glycoprotein gp120 of simian immunodeficiency virus. - Doyle, C B (1995)
The external domain of the envelope glycoprotein, gp120, of simian immunodeficiency virus (SIV) has been expressed as a mature secreted product using recombinant baculoviruses and the expressed protein, which has an observed molecular mass of 110 kDa, was purified by monoclonal antibody (MAb) affinity chromatography. N-terminal sequence analysis showed a signal sequence cleavage identity similar to that of the gp120s of both human immunodeficiency virus type 1 (HIV-1) and HIV type 2. The expressed molecule bound to soluble CD4 with an affinity that was approximately 10-fold lower than that of gp120 from HIV-1. A screening of the ability of SIV envelope MAbs to inhibit CD4 binding revealed two groups of inhibitory MAbs. One group is dependent on conformation, while the second group maps to a discrete epitope near the amino terminus. The particular role of the V3 loop region of the molecule in CD4 binding was investigated by the construction of an SIV-HIV hybrid in which the V3 loop of SIV was precisely replaced with the equivalent domain from HIV-1 MN. The hybrid glycoprotein bound HIV-1 V3 loop MAbs and not SIV V3 MAbs but continued to bind conformational SIV MAbs and soluble CD4 as well as the parent molecule.